A Short Physical Performance Battery (SPPB) como preditora da fragilidade em idosos residentes na comunidade - Câmara, Saionara Maria Aires da (2011)
Introduction: The SPPB provides information about physical function and is a predictor of adverse events in the elderly. Frailty is a multidimensional syndrome that increases susceptibility to diseases and disability. However it may be possible to prevent or postpone frailty if is identified early. Our objective is to analyze SPPB s ability in screening for frailty a community-dwelling young elderly from cities with distinct socioeconomic conditions. Methods: Data were originated from community dwelling adults (65-74 years old) in Canada (Saint Bruno; n = 60) and Brazil (Santa Cruz; n = 64). SPPB was used to assess physical performance. Frailty was defined as the presence of ≥ 3 of these criteria: weight loss, exhaustion, weakness, mobility limitation and low physical activity. One point was given for each criterion met, totalizing a frailty score ranged from 0 to 5. The Linear Regression and Receiver Operating Characteristics analyses were performed to evaluate the SPPB s screening ability. Results: Mean age was 69.48, 10.0% of the Saint Bruno s sample and 28.1% of Santa Cruz s were frail (p = 0.001), the SPPB score means were 9.6 and 8.5 respectively (p = 0.01). SPPB correlated with the frailty score (R2 = 0.33), with better results for Saint Bruno. A cutoff of 9 in SPPB had good sensitivity and specificity in discriminating frail from non frail in Saint Bruno (AUC = 0.81) but showed fair results in Santa Cruz (AUC = 0.61). Conclusion: The SPPB has moderate ability in predicting frailty among older adult s population, and is an useful test to identify people with good functionality and low frailty when SPPB scores are ≥9